Hubungan Neutrophil Lymphocyte Ratio Dengan Derajat Keparahan Kellgren-Lawrence Pada Pasien Osteoartritis Lutit di RSUD Dr. H. Abdul Moeloek - Muhammad Ricky Ramadhian; Melinda Maharani; Suryani Agustina Daulay; Khairun Nisa Berawi (JIMKI: Jurnal Ilmiah Mahasiswa Kedokteran Indonesia, 2026)
Background: Osteoarthritis (OA) is a chronic degenerative joint disease that causes pain, limited mobility, and reduced ability to perform daily activities. The severity of OA can be assessed radiologically using the Kellgren–Lawrence classification. One of the inflammatory markers used to evaluate inflammatory activity in OA is the Neutrophil Lymphocyte Ratio (NLR), which reflects the balance between neutrophils and lymphocytes. This study aimed to analyze the relationship between NLR and the radiological severity of knee osteoarthritis in female patients at Dr. H. Abdul Moeloek Hospital. Method: This study used a cross-sectional approach. The samples consisted of medical records of female patients diagnosed with knee osteoarthritis during the 2022–2025 period. Data were analyzed using univariate and bivariate analyses with the Spearman rank correlation test. Results: The Spearman test showed no significant relationship between NLR and the radiological severity of osteoarthritis (p=0.789; r=-0.041). Discussion: These findings indicate that NLR is not a dominant factor in determining the radiological severity of knee OA. This may be influenced by other factors, such as the involvement of various inflammatory mediators besides NLR and the locally limited nature of inflammation in OA. Conclusion: There was no significant relationship between NLR and the Kellgren–Lawrence radiological severity in female patients with knee osteoarthritis at Dr. H. Abdul Moeloek Hospital